Peran Guru Sejarah dalam Meningkatkan Sikap Nasionalisme Siswa Kelas XI IPS MA Darul Huda Wonodadi Blitar - Tasya Fatchiati Rizqiya; Dita Hendriani (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The attitude of today's students towards nationalism is very worrying. They often come late to school, are not solemn during the flag raising ceremony, are disobedient to teachers, do not show a caring attitude towards other students, do not show mutual respect between classmates or other students. There are still many students who do not show this applies to teachers. The role of the history teacher in learning aims to shape the character of students by instilling national values ​​that can be put into practice in everyday life. So that history teachers become leading figures who play a role in increasing students' nationalist attitudes. The aims of this research are 1) to find out the manifestation of the nationalist attitude of class faced by history teachers in increasing the nationalist attitudes of class XI IPS MA Darul Huda students. This research uses qualitative research methods, with descriptive research type. Data collection techniques are using interview techniques with related parties, observation techniques regarding objects and documentation techniques. Meanwhile, data analysis techniques use data reduction, data presentation, and drawing conclusions. The results of the research are as follows: (1) the attitude of nationalism among class Heroes are realized by students studying diligently, being disciplined when participating in school activities, using domestic products and respecting other people's opinions. (2) The role of history teachers in efforts to increase students' nationalistic attitudes. Teachers have roles as role models, mentors, teachers, inspirers, authority holders and evaluators. (3) The obstacles faced by teachers in increasing students' nationalistic attitudes are the development of globalization, family background factors different, and a wide range of student interactions.